2017
DOI: 10.1111/bju.13959
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan membranes applied on the prostatic neurovascular bundles after nerve‐sparing robot‐assisted radical prostatectomy: a phase II study

Abstract: In our experience, ChiMe applied on the NVBs after NS-RARP was feasible and safe, without compromising the duration, difficulty or complication rate of the 'standard' procedure. No patients had signs of intolerance/allergy attributable to the ChiMe and potency recovery data were encouraging. A comparative cohort would have added value to the study. The present paper was performed before Conformité Européene (CE)-mark achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In that preliminary phase II study, we showed the feasibility and safety of applying ChiMe on the NVBs. Moreover, we found a trend towards faster recovery of erectile function relative to our previous experiments [6].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In that preliminary phase II study, we showed the feasibility and safety of applying ChiMe on the NVBs. Moreover, we found a trend towards faster recovery of erectile function relative to our previous experiments [6].…”
Section: Introductionsupporting
confidence: 54%
“…In order to contribute to this field, our group published a feasibility phase II study in which ChiMes were applied at the level of NVBs at the end of NS‐RARP in 140 patients , confirming the feasibility and safety of the technique.…”
Section: Discussionmentioning
confidence: 96%
“…In the near future, the association of such a technology together with the use of new regenerative materials on the preserved NVBs will promote the morphological and functional regeneration of the neurovascular network . Indeed, if the neuronal damage can be limited to a small area, the need of nervous regeneration will be small.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interesting clinical results were obtained by Porpiglia and colleagues reporting a clinical trial in which they tested chitosan membrane, already known for its effectiveness in promoting nerve regeneration [117], as protective device for neurovascular bundles following bilateral nerve-sparing radical prostatectomy [94].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the regeneration process and the functional recovery of peripheral nerves, different artificial devices have been developed and proposed for clinical application [71,92,93]. Interestingly, the application of membranes made of another biomaterial of natural origin namely chitosan has been reported to be safe and effective on the neurovascular bundles after nerve-sparing robot-assisted radical prostatectomy, appreciating also some positive results regarding potency recovery [94].…”
Section: Application Of Chitosan Membrane To Improve the Functional Rmentioning
confidence: 99%